2018
DOI: 10.1021/acsaem.8b01651
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous CuCo2S4 Microspheres: A Novel Positive Electrode for High-Performance Hybrid Energy Storage Devices

Abstract: Demands for safer, faster, and more efficient energy storage systems have motivated researchers to design and develop new electrode materials. Ternary transition metal oxides are the electrode materials commonly investigated for application in energy storage systems. Nevertheless, the low active surface area and poor conductivity limit their electrochemical performances. In the present study, nanoporous CuCo2S4 microspheres (CCS) electrode has been successfully prepared via a facile self-template method for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…The XRD pattern of CCS/NF electrode (green pattern) demonstrates peaks at ≈16.22°, 26.73°, 31.72°, 38.03°, 47.05°, 50.13°, and 55.17°, corresponding to (111), (022), (113), (004), (224), (115) and (044) crystalline CCS planes (JCPDS Card No. 42–1450) . In the case of NMS/NF electrode (red pattern), the peaks centered at 14.13°, 33.23° and 58.53° corresponding to (002), (100) and (110) crystalline of MoS 2 (JCPDS no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD pattern of CCS/NF electrode (green pattern) demonstrates peaks at ≈16.22°, 26.73°, 31.72°, 38.03°, 47.05°, 50.13°, and 55.17°, corresponding to (111), (022), (113), (004), (224), (115) and (044) crystalline CCS planes (JCPDS Card No. 42–1450) . In the case of NMS/NF electrode (red pattern), the peaks centered at 14.13°, 33.23° and 58.53° corresponding to (002), (100) and (110) crystalline of MoS 2 (JCPDS no.…”
Section: Resultsmentioning
confidence: 99%
“…Among which, CuCo 2 S 4 (CCS) has attracted great consideration as a favorable sulfospinel for SCs. Abdi et al . fabricated a CCS via a hydrothermal strategy with satisfied C s of 1566 F g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Among various transition metals 17 , nickel, manganese, and cobalt are promising in the field of supercapacitors due to their high electrochemical activity and low cost as well as the abundance of their oxide/hydroxide compounds 18 – 24 . It has also been demonstrated that the spinel ferrites of these metals (MFe 2 O 4 , M is a transition metal) deliver much better electrochemical performance due to their richer valence electron, different redox states, synergistic effects between their metal ions, electrochemical stability, and chemical and mechanical stability, suitable for batteries and supercapacitors 14 , 25 29 . Recently, we have compared the supercapacitance of MnFe 2 O 4 , CoFe 2 O 4 , and NiFe 2 O 4 nanoparticles, and found that MnFe 2 O 4 exhibits better supercapacitance properties 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all the CV proles practically have homologous appearances, which demonstrates that the fabricated ASC device delivers notable reversibility and rate capability. 37 The GCD proles shown in Fig. 6b display a symmetrical under different current densities, representing the superior rate capability and electrochemical reversibility of the ASC device.…”
Section: Resultsmentioning
confidence: 96%